1999
DOI: 10.1136/adc.80.3.248
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant treatment for acute respiratory distress syndrome

Abstract: Objective-To determine prospectively the eYcacy of surfactant in acute respiratory distress syndrome. Study design-Twenty patients, 1 month to 16 years of age, diagnosed with an acute pulmonary disease with severe hypoxaemia (PaO 2 /FiO 2 < 100) (13 with systemic or pulmonary disease and seven with cardiac disease) were treated with one to six doses of 50-200 mg/kg of porcine surfactant administered directly into the trachea. The surfactant was considered to be eVective when the PaO 2 /FiO 2 improved by > 20%.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 28 publications
2
26
1
2
Order By: Relevance
“…A significant number of clinical studies have reported benefits following the instillation of exogenous surfactants to term infants, children, or adults with ALI/ARDS or related acute respiratory failure [25,[120][121][122][123][124][125][126][127][128][129][130][131][132][133][134][135] (Table 4). However, many of these are small case series or pilot studies, and found only improvements in acute lung function (oxygenation).…”
Section: Current Studies On Surfactant Replacement Therapy In Patmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant number of clinical studies have reported benefits following the instillation of exogenous surfactants to term infants, children, or adults with ALI/ARDS or related acute respiratory failure [25,[120][121][122][123][124][125][126][127][128][129][130][131][132][133][134][135] (Table 4). However, many of these are small case series or pilot studies, and found only improvements in acute lung function (oxygenation).…”
Section: Current Studies On Surfactant Replacement Therapy In Patmentioning
confidence: 99%
“…Studies of surfactant therapy in children and adults with ALI/ARDS show positive results in a number of case reports or relatively small pilot trials [120,121,[124][125][126][127][128]. However, particularly in adults, controlled clinical trials have been less successful.…”
Section: Current Studies On Surfactant Replacement Therapy In Patmentioning
confidence: 99%
“…A number of uncontrolled and controlled studies have documented clinical benefit from exogenous surfactant replacement therapy in term infants, children, and adults with acute respiratory failure (ALI/ARDS) [66][67][68][69]154,[186][187][188][189][190][191][192][193][194][195][196][197][198][199][200] ( Table 2). Of the 19 positive studies listed in Table 2, 9 were controlled trials [67][68][69]154,192,[197][198][199][200] and 10 were uncontrolled treatment trials, in which the risk of selection bias is inherent.…”
Section: Human Studiesmentioning
confidence: 99%
“…A dose-related response, more evident with higher doses (200 mg/kg) than with lower ones (50 mg/kg), was reported in 10/13 children with severe ARDS not responding to conventional ventilation. 12 Further studies are needed to demonstrate whether early use of surfactant does improve the prognosis of ARDS, which is still extremely poor, with a case-fatality ratio exceeding 40%. With regard to the choice of a 'permanent' therapy, in our case BMT was an elective procedure, performed when the patient's overall condition was good, with normal results of liver function tests.…”
Section: Discussionmentioning
confidence: 99%